HLA-DRB1*03 And DRB1*15 Frequency In Helicobacter Pylori Superficial Gastritis - Salih, Wafaa Hazim (AL-Kindy College Medical Journal, 2019)
Background: Background: Helicobacter pylori is an important gastrointestinal bacteria related to the development of superficial atrophic gastritis, peptic ulcer and gastric cancer. Human leukocyte antigens (HLA) may play an important roles in host immune responses to H pylori antigens. Aim of the study: to investigate the association between HLA-DRB1 genotypes and superficial gastritis with H. pylori infection in an Iraqi patients. Patients and methods: Sixty patients with superficial gastritis and 100 individuals with apparently normal results after endoscopic examination were recruited from Al-Kindy Teaching Hospital - Gastrocolonoscope Unit between January 2014 and July 2016. All study patients and controls group underwent upper gastrointestinal endoscopic examinations. They were analyzed for CagA antibodies Immunoglobulin G (IgG) for H. pylori and HLA Class II genotyping (HLA-DRB1). Results: Patients with superficial gastritis with H pylori. The infection showed significant expression (P=0.0001) DRB1*03:01 genotypes and DRB1*15:01 (P= 0.004) as compared to control group. Conclusions: Genetic factor may play a role in gastritis. HLA-DRB1*03 and HLA-DRB1*15 may increased the susceptibility to superficial gastritis in H pylori infected patients.